DOI: 10.11606/t.11.2018.tde-22032018-163516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fat source on beef quality

Abstract: I will always be grateful to those who contributed to my professional development in the earlier stages of my career. I could not achieve my goals without their help and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Wheeler and Koohmaraie (1999) report that sarcomere length from nonshortened LD was 1.69 μm, compared with those that were cold shortened, at 1.36 μm. Other studies focusing on the feeding of distillers grains have also reported no differences in sarcomere length (Chao et al, 2017;Ribeiro, 2017).…”
Section: Sarcomere Lengthmentioning
confidence: 92%
“…Wheeler and Koohmaraie (1999) report that sarcomere length from nonshortened LD was 1.69 μm, compared with those that were cold shortened, at 1.36 μm. Other studies focusing on the feeding of distillers grains have also reported no differences in sarcomere length (Chao et al, 2017;Ribeiro, 2017).…”
Section: Sarcomere Lengthmentioning
confidence: 92%